Field Evaluation of In Vitro Derived Mutants of Different Varieties of Banana on Fruit Quality Parameters - Kirankumar, K. H.; Prakasha, D.P.; Kulapati, H.; Prabhuling, G.; Basavarajappa , M.P.; Sanjeevraddi, G. R.; Jameel, J. (International Journal of Bio-resource and Stress Management, 2023)
A field experiment was conducted on field evaluation of in vitro derived mutants of different varieties of banana during (October–September), 2018–19 and (September–August), 2019–20 at the Department of Fruit Science, College of Horticulture, University of Horticultural Sciences, Bagalkot, Karnataka, India. The one thirty-eight (138) in vitro derived banana mutants both physical and chemical mutagens treated plants along with check were planted. The experiment was laid out in augmented block design with 6 blocks and 26 subplots each block having 23 in vitro mutant lines and three checks. The cultivars used for the experiment were viz., Yelakki bale, Rajapuri bale and Nanjangud rasabale. Among 138 in vitro derived mutants in plant crop, there was no significant difference noted in pulp weight, pulp to peel ratio and fruit firmness. Among different mutants in pulp weight parameter the maximum pulp weight was recorded in NR45Gy-09 (86.45 g), peel weight, RAJ45Gy-14 (20.00 g) pulp to peel ratio YB35Gy-05 (6.70) flavour acceptance, YB40Gy-03 (7.82) fruit firmness, YB40Gy-12 (18.82 N) and shelf life YB40Gy-14 (8.10 days). in ratoon crop, the maximum pulp weight was recorded in NR45Gy-09 (86.45 g), peel weight, RAJ45Gy-14 (25.00 g) pulp to peel ratio, YB35Gy-24 (7.36) flavour acceptance, RAJ45Gy-03 (7.48) fruit firmness, YB40Gy-11 (16.50 N) and shelf life YB45Gy-08 (9.00 days).